Air Pollution Modelling: Local-, Regional-, and Global-Scale Application - Itahashi, Syuichi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The air pollution problem inevitably accompanies our human activities. Severe air pollution situations have been reported, especially in emerging countries, and satisfying the air quality standards fully remains an underlying issue. Today, modeling research is one of the more valuable approaches to understanding the behavior of air pollutants, and is useful for regulation-, policy- and decision-making. Such modeling applications range, with regard to horizontal grid resolution, from a few km (local) to hundreds of km (regional), to thousands of km (global). To foster our current scientific knowledge on modeling potentialities and limitations, scientific research related to multi-scale air pollution modeling is collected in this book.